Setting the regulatory agenda: Statutory deadlines, delay and responsiveness - Bertelli, Anthony M.; Doherty, Kathleen M. (Public Administration Review)
Congress imposes statutory deadlines in an attempt to influence agency regulatory agendas, but agencies regularly fail to meet them. What explains agency responsiveness to statutory deadlines? Taking a transaction cost politics approach, the authors develop a theory of responsiveness to deadlines centered on political feasibility to explain how agency managers map rulemaking onto calendar and political time. This theory is tested on all unique rules with statutory deadlines published in the Unified Agenda of Federal Regulatory and Deregulatory Actions between 1995 and 2012. The argument and findings about the timing and ultimate promulgation of rules have implications that reorient the study of the regulatory agenda from legal and political into more managerial terms. - Reproduced.